Hepatitis C Virus (HCV) Infection, the Importance of Genotyping - Kadhim, Iman Jabbar; Rasheed, Suaad Muhammed H.; Al-Kraity, Wijdan Rajh Hamza; Deli, Falah Abdulhasan (Medical Science Journal for Advance Research, 2025)
Hepatitis C virus (HCV) is an enveloped, single stranded positive-sense RNA virus discovered in the late eighties, circulating HCV antibody (anti-HCV) aided in diagnosis and screening of blood products minimizing post blood transfusion spread to a large extent, it is still highly prevalent in underdeveloped areas and it contribute largely to chronic liver diseases and hepatocellular carcinoma, One of the important features of HCV is its prominent genetic variability where new genetic polymorphism are emerging frequently and this has a great impact on treatment deciissions including the emergence of drug resistant strains among difeerent genotypes specially genotype 3, accordingly the Direct-Acting Antivirals (DAAs) including NS3/4A protease inhibitors, NS5A inhibitors and NS5B polymerase inhibitors are used in combination for patients initially treated and for those who have regimen failure. Unfortunately, still the studies of polymorphism and drug susceptibilities in Iraq are scarce and deficient.